2019
DOI: 10.1136/bcr-2019-229208
|View full text |Cite
|
Sign up to set email alerts
|

Man with epigastric pain and persistently elevated serum lipase

Abstract: Serum lipase and amylase are commonly requested in individuals presenting with abdominal pain for investigation of acute pancreatitis. Pancreatic hyperenzymaemia is not specific for acute pancreatitis, occurring in many other pancreatic and non-pancreatic conditions. Where persistent elevation of serum lipase and amylase occurs in the absence of a diagnosed cause or evidence of laboratory assay interference, ongoing radiological assessment for pancreatic disease is required for 24 months before a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…These findings confirmed that these parameters are vital surrogate markers to determine the organic diseases of the GI tract, such as persistent intestinal infection, intestinal inflammation, celiac disease, and IBD [ 15 23 ]. Levels of serum pancreatic enzymes, namely, amylase and lipase, were likely to be increased in non-pancreatic disorders or conditions such as intestinal inflammation, gut obstruction, duodenal ulceration, coeliac disease, peritonitis, acute cholecystitis, renal insufficiency, head injury, burns, shock, diabetic ketoacidosis, and a critical illness [ 24 25 ], which could be possible causes for increased pancreatic enzyme levels. Our study reported a significant rise in serum lipase levels among children with abnormal endoscopy due to various possible co-incidences.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirmed that these parameters are vital surrogate markers to determine the organic diseases of the GI tract, such as persistent intestinal infection, intestinal inflammation, celiac disease, and IBD [ 15 23 ]. Levels of serum pancreatic enzymes, namely, amylase and lipase, were likely to be increased in non-pancreatic disorders or conditions such as intestinal inflammation, gut obstruction, duodenal ulceration, coeliac disease, peritonitis, acute cholecystitis, renal insufficiency, head injury, burns, shock, diabetic ketoacidosis, and a critical illness [ 24 25 ], which could be possible causes for increased pancreatic enzyme levels. Our study reported a significant rise in serum lipase levels among children with abnormal endoscopy due to various possible co-incidences.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the very extensive Italian cases, reports in other countries are limited. In literature, few cases are reported in Japan [4,11], Belgium [14], USA [17,33], India [34], Taiwan [35], Brazil [36], Austria [37], Poland [38], Ukraine [39], Australia [40], Spain [41,42], Venezuela [43], Morocco [44], and Germany [45].…”
Section: Key Points Y the Increase In Serum Amylase And/or Lipase Affmentioning
confidence: 99%